"On tuskallista, kun apu venyy kuukausien päähän" : korkeakouluopiskelijoiden kokemuksia Ylioppilaiden terveydenhoitosäätiön (YTHS) mielenterveyspalveluihin pääsystä - Risikko, Jani (2024)
Mental health problems among university students have significantly increased; in Finland, one in three university students suffers from anxiety and depressive symptoms. Consequently, the demand for mental health services for university students has tripled over the past three years. The Finnish Student Health Service (FSHS), which is responsible for the healthcare of university students, has been unable to meet the increased demand for services. This study aimed to investigate the experiences of university students regarding access to FSHS mental health services from the perspective of waiting times.